Are transition economy workers underpaid? - Vera A. Adamchik; Josef C. Brada; Arthur E. King (Osteuropa-Institut Regensburg, 2009)
We examine the extent to which workers in transition and developed market economies are able to obtain wages that fully reflect their skills and labor force characteristics. We find that workers in two transition economies, the Czech Republic and Poland, are able to better attain the maximum wage available than are workers in a sample of developed market economies. This greater wage-setting efficiency in the transition economies ap-pears to be more the result of social and demographic characteristics of the labor force than of the mechanisms for setting wages or of labor market policies.
Keywords: J31; P23; 330; labor markets; wage inefficiency; job search; stochastic frontier; economic transition; Lohnbildung; Lohn; Übergangswirtschaft; Technische Effizienz; Schätzung; Tschechische Republik; Polen